Games, strategies, and decision making - Harrington, Joseph Emmett, 1957- (New York : Worth, 2009)
This book on game theory introduces and develops the key concepts with a minimum of mathematics. Students are presented with empirical evidence, anecdotes and strategic situations to help them apply theory and gain a genuine insight into human behaviour. The book provides a diverse collection of examples and scenarios from history, literature, sports, crime, theology, war, biology, and everyday life. These examples come with rich context that adds real-world meat to the skeleton of theory. Each chapter begins with a specific strategic situation and is followed with a systematic treatment that gradually builds understanding of the concept.
Introduction to Strategic Reasoning -- Building A Model of A Strategic Situation -- Eliminating the Impossible:Solving A Game When Rationality is Common Knowledge -- Stable Play: Nash Equilibria in Discrete Games with Two Or Three Players -- Stable Play:Nash Equilibria in Discrete N-Player Games -- Stable Play: Nash Equilibria in Continuous Games -- Keep 'Em Guessing: Randomized Strategies -- Taking Turns: Sequential Games of Perfect Information -- Taking Turns in the Dark: Sequential Games of Imperfect Information -- I Know Something You Don't Know: Games with Private Information -- What You Do Tells Me Who You Are: Signaling Games -- Lies and the Lying Liars that Tell Them: Cheap Talk Games -- Playing Forever: Repeated Interaction with Infinitely-Lived Players -- Cooperation and Reputation: Applications of Repeated Interaction with Infinitely-Lived Players -- Interaction in Infinitely-Lived Institutions -- Evolutionary Game Theory and Biology: Evolutionarily Stable Strategies -- Evolutionary Game Theory and Biology: Replicator Dynamics.
Includes bibliographical references and index.
Keywords: Game theory -- Decision making; Decision making; Games of strategy (Mathematics); Game theory; Economics, Mathematical; Decision making -- Mathematics; Strategic planning -- Mathematics; Game theory; Economics, Mathematical; Decision making -- Mathematics; Strategic planning -- Mathematics; Speltheorie; Besluitvorming; Spieltheorie; Theorie; Spieltheorie; Decision making -- Mathematics; Economics, Mathematical; Game theory; Strategic planning -- Mathematics